Trends in health behaviors and mental health among Korean adolescents in Korea over 5 years, 2017–2021: focusing on the comparisons before and during the COVID-19 pandemic - Lee, Mi-Sun; Kim, Dong Jun; Lee, Hooyeon (Frontiers in Public Health, 2023)
Objectives: We investigated recent trends in health behaviors and mental health conditions among Korean adolescents from 2017 to 2021 and compared the changes before and during the coronavirus disease 2019 (COVID-19) pandemic. Methods: Data analysis was conducted on 289,415 adolescents participating in the Korea Youth Risk Behavior Web-Based Survey, an annual cross-sectional study from 2017 to 2021. All analysis was conducted using sex stratification, and the annual percentage change (APC) was calculated. Results: Alcohol consumption and smoking decreased in the first year of the COVID-19 pandemic compared with before, except for girls from the low-income level. The prevalence of inadequate physical activity for both boys and girls increased in 2020 compared with the pre-COVID-19 period and decreased again by 2021. The prevalence of obesity in both sexes increased regardless of the period (boys, APC=8.2%, 95% confidence intervals (CI), 6.4–10.1; girls, APC=3.3%, 95% CI, 1.8–4.8). The prevalence of stress, depression, and suicidal ideation, plans, and attempts for both sexes decreased in 2020 compared to the pre-COVID-19 period. By 2021, this prevalence had returned to a level similar to before the pandemic. No significant APC changes were observed in the prevalence of mental health. Conclusions: These findings demonstrate the trends and APCs in health behaviors and mental health conditions among Korean adolescents over the last 5 years. We must pay attention to the heterogeneous and multifaceted features of the COVID-19 pandemic.